Pengaruh Kualitas Pelayanan dan Harga Terhadap Kepuasan Konsumen pada Toko Libra Komputer Di Kota Luwuk: The Effect of Service Quality and Price on Consumer Satisfaction at the Libra Computer Store in Luwuk City - Deviana Peuk; Arpan Kurubit; Ichsan Milang (Jurnal Ilmiah Produktif, 2019)
This study aims to determine the quality of service influences consumer satisfaction in Libra Computers in Luwuk City, To find out prices have an influence on consumer satisfaction in Libra Computers in Luwuk City, and To find out service quality and prices have an influence on consumer satisfaction on Libra Computers in Luwuk City Luwuk. The analytical method used in this study is multiple linear regression analysis using 100 samples taken using the accidental sampling technique. Based on the results of research and testing, it is concluded that service quality and price alone (partial) influence consumer satisfaction at the Libra Computer Store in Luwuk, while simultaneously (simultaneous) service quality and price influence consumer satisfaction at the Libra Computer Store in Luwuk. Luwuk. Meanwhile, the close relationship between service quality and price on consumer satisfaction at the Libra Computer Store in Luwuk is in the medium category, and the contribution or contribution of service quality and price to consumer satisfaction at the Libra Computer Store in Luwuk i s 22 . 3 % , whi l e t h e r e s t i s 77 . 7 % i s i n f l ue nced by ot h e r f a c t o r s  not exami ne d.